2012
DOI: 10.1039/c2py20380d
|View full text |Cite
|
Sign up to set email alerts
|

Triggered insulin release studies of triply responsive supramolecular micelles

Abstract: The synthesis of a supramolecular double hydrophilic glucose responsive block copolymer (DHBC) held together by cucurbit [8]uril (CB[8]) ternary complexation and its subsequent self-assembly into micelles is described. The supramolecular block copolymer assembly consists of poly(Nisopropylacrylamide) (PNIPAAm) and poly(acrylamidophenyl boronic acid) (PAAPBA) as temperature and glucose responsive blocks, respectively, and poly(dimethylacrylamide) (PDMAAm) as a hydrophilic block. Drug release studies of insulin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 50 publications
(145 reference statements)
0
38
0
Order By: Relevance
“…It was found that the hydrophilic PDMAAm segments could be removed from the micelles in the presence of the adamantaneamine, resulting in rupture of the micellar superstructures and enabling complete release of insulin from the hierarchical micelles. The most important feature was that this system displayed a pulsated release of insulin with the three different triggers of temperature, glucose, and a competitive guest, and would have potential for insulin therapies and the treatment of diabetes in “on‐demand'' release 144…”
Section: Multi‐stimuli‐responsive Particlesmentioning
confidence: 99%
“…It was found that the hydrophilic PDMAAm segments could be removed from the micelles in the presence of the adamantaneamine, resulting in rupture of the micellar superstructures and enabling complete release of insulin from the hierarchical micelles. The most important feature was that this system displayed a pulsated release of insulin with the three different triggers of temperature, glucose, and a competitive guest, and would have potential for insulin therapies and the treatment of diabetes in “on‐demand'' release 144…”
Section: Multi‐stimuli‐responsive Particlesmentioning
confidence: 99%
“…The macrocyclic host, cucurbit [7]uril (CB [7]) was chosen as the model. Cucurbit[n]urils (CB[n]s) are a family of water-soluble macrocyclic hosts, which have a hydrophobic cavity capable of the binding of one or two guest molecules depending on the size of di®erent CB[n]s. [22][23][24] CB [7] possesses good solubility in water and strong a±nity for one guest molecule. [25][26][27][28][29][30][31] The authors employed CB [7] to bind with the positive charge and hydrophobic component on "-poly-l-lysine hydrochlorides to construct the polypseudorotaxane for antibacterial regulation.…”
Section: Responsive Antibacterial Materialsmentioning
confidence: 99%
“…Besides CD‐based supramolecular systems, cucurbit[8]uril (CB[8]) ternary complexation with bioresponsive multiple‐block copolymers has also attracted many interests recently. We reported that block copolymer, containing temperature sensitive PNIPAAm block, glucose responsive poly(acrylamidophenyl boronic acid) (PAAPBA) block, and poly(dimethylacrylamide) (PDMAAm) as hydrophobic block could act as insulin carrier and release insulin drug upon triggers of temperature, high glucose concentration, and addition of CB[8] as competitive guest, indicating its potential drug delivery application for diabetic treatment. Further investigation revealed that a copolymer consisting of special end‐functionalised PNIPAAm and pH sensitive PDMAEMA could self‐assemble with CB[8] to form bioresponsive supramolecules, with the ability to triply trigger the release of encapsulated doxorubicin and effectively induce HeLa cell viability reduction in terms of temperature, pH, and competitive CB[8] amount .…”
Section: Designing Thermoresponsive Molecular Building Blocks For a Bmentioning
confidence: 99%